Comparative Study of Magnetic Pc1 Pulsations between Low Latitudes and High Latitudes: Statistical Study - Kuwashima, Masayuki; Toya, Takeshi; Kawamura, Makoto; Hirasawa, Takeo; Fukunishi, Hiroshi; Ayukawa, Masaru (1981)
P(論文) Statistical features of Pc1 pulsations are studied on the basis of data obtained at low- and high-latitude stations, Memambetsu in Japan and Syowa Station in Antarctica, during the period from January 1977 to January 1979. The observed features of high-latitude Pc1 can be divided into three groups, i.e., HM chorus, periodic emission and others (IPDP, Morning IPDP, dot, etc.). For the periodic emission, the generation mechanism is expected to be common to low and high latitudes. departmental bulletin paper